Prevalence of Pelvic Incontinence in Patients With Cystic Fibrosis - Fatima Neemuchwala MD; Fahmida Ahmed BS; Samya Z. Nasr MD, CPI (SAGE Publishing, 2017)
Cystic fibrosis (CF) patients are at risk for developing pelvic (urinary and/or fecal) incontinence due to progressive weakness of pelvic floor muscles secondary to recurrent episodes of coughing and respiratory infections. Many patients do not bring these symptoms to the attention of their health care providers because of social embarrassment and lack of knowledge of available effective treatment. Several studies have identified the prevalence of incontinence in CF adults and adolescents. However, few studies identified the problem in children with CF. Our study aims are to identify the prevalence of pelvic incontinence in CF patients aged 6 to 21 years, to identify the correlation between incontinence and severity of lung disease, and to help develop treatment strategy in collaboration with physical therapy to address these issues.